Strengthening SPMI in Increasing the Competitiveness of Islamic Higher Education in the Era of Globalization - Slamet Setiawan; Diana Faridatul Khasanah; Arinda Firdianti; Abdul Muhith (International Journal of Islamic Educational Research, 2024)
This study examines the role of the Internal Quality Assurance System (SPMI) in enhancing the competitiveness of Islamic Higher Education Institutions (PTI) in the era of globalization. The purpose of the research is to understand how SPMI can improve the quality of education, research, and graduates in PTI. The method used is a qualitative approach with a descriptive design, through case studies of several PTIs that have implemented SPMI. The results show that the application of SPMI significantly contributes to improving academic quality and the competitiveness of PTIs. Strategies for strengthening SPMI that involve enhancing internal capacity, academic innovation, and international collaboration are key to success. This research recommends that PTIs strengthen their commitment to SPMI through targeted policies and conduct ongoing evaluations to maintain educational quality. The implications of this study emphasize the importance of SPMI in building the global competitiveness of PTIs, as well as in creating graduates who are prepared to face the challenges of the job market.